The Role of Islamic Religious Education Teachers in Forming Students' Disciplined and Responsible Characters - Hapsariningrum, Novia; al-Wasewi, Ibrahim Haruna Hassan; Esmaeili, Zeinab (Cahaya Ilmu Cendekia Publisher, 2025)
Purpose of the study: The purpose of this study is to determine the role of Islamic Religious Education teachers in efforts to form a disciplined character, the role of Islamic Religious Education teachers in efforts to form a responsible character, and the supporting and inhibiting factors in efforts to form a disciplined and responsible character in the school. Methodology: This research is a qualitative descriptive study. The subjects of the study were the principal, vice principal, teachers, and students. Data collection was done by interview. Main Findings: The results of the study showed that Islamic Religious Education teachers in efforts to form disciplined and responsible characters showed their roles, namely: the role as educators, acting as models and role models, and the role as motivators. In efforts to form these characters, there are supporting and inhibiting factors in their implementation. Supporting factors come from teachers, parents, and the environment. Then the inhibiting factors come from peers. Novelty/Originality of this study: The results of this study provide a new perspective on the effectiveness of the role of Islamic Religious Education teachers as agents of character formation for students through a value-based education approach that is integrated into teaching and learning activities.